2001
DOI: 10.1104/pp.127.4.1539
|View full text |Cite
|
Sign up to set email alerts
|

Brachypodium distachyon. A New Model System for Functional Genomics in Grasses

Abstract: A new model for grass functional genomics is described based on Brachypodium distachyon, which in the evolution of the Pooideae diverged just prior to the clade of "core pooid" genera that contain the majority of important temperate cereals and forage grasses. Diploid ecotypes of B. distachyon (2n = 10) have five easily distinguishable chromosomes that display high levels of chiasma formation at meiosis. The B. distachyon nuclear genome was indistinguishable in size from that of Arabidopsis, making it the simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
279
1
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(295 citation statements)
references
References 20 publications
9
279
1
6
Order By: Relevance
“…Interest in the genus increased when initial molecular study (Shi et al 1993;Catalan and Olmstead 2000) revealed its close phylogenetic proximity with agronomically important cereals such as wheat and barley. Additionally, microdensitometric and flow cytometry measurements proved Brachypodium species to have very low nuclear DNA content (Draper et al 2001;Bennett and Leitch 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interest in the genus increased when initial molecular study (Shi et al 1993;Catalan and Olmstead 2000) revealed its close phylogenetic proximity with agronomically important cereals such as wheat and barley. Additionally, microdensitometric and flow cytometry measurements proved Brachypodium species to have very low nuclear DNA content (Draper et al 2001;Bennett and Leitch 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the inbreeding annual weedy grass Brachypodium distachyon has been proposed as a species of choice for comparative genomic studies of its less tractable but agronomically important relatives (Draper et al 2001;Jenkins et al 2003Jenkins et al , 2005. The potential of B. distachyon as a model plant has been supported by studies demonstrating its high capacity for cell culture, transformation, and regeneration (Bablak et al 1995;Christiansen et al 2005), efficiency in mutagenesis procedures (Draper et al 2001;Engvild 2005), and usefulness in studies of plant-pathogen interactions (Routledge et al 2004;Allwood et al 2006) as well as functional analyses of genes (Olsen et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Th erefore, a model system for forage grasses and cereal crops was required to provide more general genomic data for grasses, which may aid in the identifi cation of genes of agronomic interest (Keller and Feuillet 2000). Brachypodium distachyon , a member of the Pooideae subfamily, is a wild annual grass that possesses several traits that make it an ideal model organism for the study of temperate cereals, including small size, rapid generation time, a small genome, diploid accessions, and simple growth requirements (Draper et al 2001). Highly effi cient transformation methods have been developed, and B. distachyon germplasm has been collected for morphological and cytological analyses (Scoles et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The Brachypodium embryo is almost identical to the embryos of barley and wheat anatomically. This wild grass is a model for temperate cereals and forage grasses due to its numerous valuable features, such as its small stature and genome size and short life cycle, which make it suitable for laboratory research [28]–[30]. Recently, Barrero et al [24] proposed Brachypodium as an ideal model for studies of grain dormancy in grasses and recommended that it be used to identify new strategies for increasing grain dormancy in crop species.…”
Section: Introductionmentioning
confidence: 99%